2022
DOI: 10.1002/cam4.5206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of anamorelin in patients with cancer cachexia: Post‐hoc subgroup analyses of a placebo‐controlled study

Abstract: Background Cachexia, a disorder associated with anorexia, inflammation, and muscle wasting, is frequent in cancer patients. We performed post‐hoc analyses of the ONO‐7643‐04 study to investigate the efficacy and safety of anamorelin in subgroups of Japanese patients with non‐small cell lung cancer (NSCLC). Methods The patients were divided into subgroups by baseline characteristics, including sex, age, body mass index, prior weight loss, performance status (PS), concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…According to the subgroup effectiveness analysis by patient background characteristics, most of the subgroups showed tendencies towards increases in BW and appetite from baseline (Table S6 , S7 ), although patients with a BMI <20 kg/m 2 showed a greater BW gain than patients with a BMI ≥20 kg/m 2 . Post hoc subgroup analyses of the ONO‐7643‐04 trial revealed that the odds ratio for BW improvement in the anamorelin arm vs. placebo arm tended to be greater in patients with a BMI of <20 kg/m 2 at baseline than in those with a BMI of ≥20 kg/m 2 , 22 consistent with the current results. Although an increased appetite was observed regardless of baseline BMI, a baseline BMI of <20 kg/m 2 may be useful as a predictor of BW gain in patients treated with anamorelin.…”
Section: Discussionsupporting
confidence: 87%
“…According to the subgroup effectiveness analysis by patient background characteristics, most of the subgroups showed tendencies towards increases in BW and appetite from baseline (Table S6 , S7 ), although patients with a BMI <20 kg/m 2 showed a greater BW gain than patients with a BMI ≥20 kg/m 2 . Post hoc subgroup analyses of the ONO‐7643‐04 trial revealed that the odds ratio for BW improvement in the anamorelin arm vs. placebo arm tended to be greater in patients with a BMI of <20 kg/m 2 at baseline than in those with a BMI of ≥20 kg/m 2 , 22 consistent with the current results. Although an increased appetite was observed regardless of baseline BMI, a baseline BMI of <20 kg/m 2 may be useful as a predictor of BW gain in patients treated with anamorelin.…”
Section: Discussionsupporting
confidence: 87%
“…Takayama and others conducted secondary analyses of trial ONO-7643-04, a study in lung cancer patients. These analyses showed that, among 81 anamorelin-treated patients and 90 placebo-exposed patients, anamorelin resulted in appetite improvement compared to baseline, even in various subgroups based on age, gender, and other baseline demographic factors [14]. Although some of these subgroups might have been represented with small patient numbers and hence might have led to underpowered analyses, overall, it appears that anamorelin seems uniform across patients in its ability to promote appetite in patients with non-small-cell lung cancer.…”
Section: An Update On Palliation Of Anorexiamentioning
confidence: 97%
“…Furthermore, anamorelin was well tolerated. Recently, Takayama et al 32 showed that, among 81 anamorelin-treated patients and 90 placebo-exposed patients, anamorelin resulted in appetite improvement from baseline, even in age- and sex-based subgroups, observations that suggest this agent has the potential of helping a broad swath of patients with advanced cancer, if prescribed.…”
Section: Have Advanced Cancer I'm Not Hungry and I'm Losing Weight Wh...mentioning
confidence: 99%